Recruitment of diverse community health center patients in a pragmatic weight gain prevention trial - Hailey N. Miller; Miriam B. Berger; Sandy Askew; Melissa C. Kay; Miriam Chisholm; Gaurav Sirdeshmukh; Christina M. Hopkins; Ashley Brewer; Abigail DeVries; Marni Holder; Gary G. Bennett (Journal of Clinical and Translational Science, 2023)
Abstract